A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species - Stępień, A.; Błachowiak-Samołyk, K.; Krawczuk, M.; Angel, M.v. (Zootaxa, 2018)
The halocyprid ostracod genus Boroecia Poulsen, 1973 is described in detail and Boroecia borealis (Sars, 1866) is nominated as type species. We unravel several taxonomic confusions and uncertainties in the earlier literature that had their origins in the classification of Boroecia maxima and Boroecia antipoda (Müller, 1906) as subspecies of Boroecia borealis. Three new species are described, B. alaska n. sp., and B. danae n. sp. from the Pacific and B. hopcrofti n. sp. from the high Arctic, bringing the total number of species in the genus to six. Five of the species are described in detail, the only exception is Boroecia maxima (Brady & Norman, 1896), for which there is already a full description in the literature. Comparative illustrations are provided for all the species together with standardised meristic data. A key to the identity all six species is included.